Mediation Analysis of Supply Chain Integration on the Relationship of Quality, Flexibility and Delivery with Innovation Performance - Aini, Nur; Sunarti, Sunarti (International Journal of Supply Chain Management, 2020)
The basic objective of the current article is to analyze the impact of quality, flexibility and delivery on the innovation performance of the Fish Streat Jabodetabek, Indonesia. The aim also shows the investigation of the mediating role of supply chain integration among the links of quality, flexibility, delivery and innovation performance of the Fish Streat Jabodetabek, Indonesia. The data of the present study has gathered by using a questionnaire from the employees working in Fish Streat Jabodetabek while data analyze by using the smart-PLS. The results revealed that quality and flexibility have positively associated with innovation performance. The findings also show that supply chain integration positively mediates among the links of quality, flexibility, delivery and innovation performance. These findings are valuable for policy developers who develop the policies on the supply chain integration and innovation performance along with the upcoming researchers who want to examine this area in future.